FENOMENA SASTRA CYBER: TREND BARU SASTRA ISLAMI DALAM MASYARAKAT MODERN DI INDONESIA - Cinthya, Nathasha; Wati, Rianna (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2020)
Abstract:The existence of the internet in the era of technology as now has an extraordinary influence on the world community. The internet contains various insights into knowledge and information and gave birth to new terms in various fields, one of which is in the field of literature, namely cyber literature or cyber literature. The scope of literature in the cyber world is broad and varied because it involves the global community. Don’t want to be left behind, Islamic religious literary genre also contributes in the literary treasures in the cyber world with Islamic literary works published by the author on blogs, sites, application media, and other social media networks. The existence of various pages of Islamic cyber-nuanced literature creates a new trend in the digital technology user community in Indonesia. This journal presents a discussion of Islamic religious literary trends in the cyber realm in the Indonesian population. This research uses a qualitative study with descriptive analysis. The results of this study reveal the trend of the Islamic literary genre in cyber literature in Indonesia